SENSORY EVALUATION OF CHERRY AND SOUR CHERRY FRUITS (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The competitiveness of fruit products is determined by their external and sensory properties, among which the key ones are weight, diameter, colour, hardness, texture, taste, and aroma. For fresh fruits such as sweet cherries and cherries, sensory appeal is a key indicator of consumer value and commercial quality for both raw materials and processed products. The following sensory characteristics influence the tasting card for the professional assessment of cherry quality: external fruit appearance, consistency, and taste. The sensory profile of the fruit is influenced by its size, shape, colour, pulp consistency and juiciness, the nature of its skin and individual flavour nuances. To determine the sensory evaluation of sweet cherry fruits, model varieties of three ripening periods were selected: 1st (early) – ‘Sweet Early’, ‘Merchant’, ‘Biharro Burlat’, ‘Rubinova Rannia’, ‘Valerii Chkalov’, ‘Kazka’, ‘Zabuta’; 2nd (medium) – ‘Kordia’, ‘Octavia’, ‘Vynka’, ‘Pervystok’, ‘Temp’, ‘Liubymytsia Turovtseva’, ‘Talisman’, ‘Dilema’, ‘Melitopolska Chorna’; ‘Orion’, ‘Chervneva Rannia’, ‘Dachnytsia’, ‘Prostir’; 3rd (late) – ‘Karina’, ‘Regina’, ‘Mirazh’, ‘Krupnoplidna’, ‘Udivitielna’, ‘Zodiak’, ‘Surpryz’, ‘Kolhoznytsia’, ‘Kosmichna’, ‘Prazdnichna’, ‘Anons’, ‘Tempion’, ‘Meotyda’. For the experiment, fruits of 10 model cherry varieties were taken: ‘Vstriecha’, ‘Ozhydanije’, ‘Shalunia’, ‘Siyanets Turovtsovoi’, ‘Griot Melitopolskyi’, ‘Solidarnist’, ‘Ihrushka’, ‘Melitopolska Purpurna’, ‘Modnitsa’, and ‘Ekspromt’. Sensory evaluation of sweet cherry and cherry fruits was conducted during consumer ripeness. The highest sensory rating (9,0) was given to the cherry varieties ‘Kazka’, ‘Vynka’, and ‘Krupnoplidna’. In terms of taste, the maximum score (9,0) was given to the varieties ‘Kazka’ and ‘Merchant’ for their harmonious sweet-and-sour taste and distinct aroma. The best consistency (8,9) was demonstrated by the Vinka variety with its tender, juicy flesh and thin, dense skin. Experts noted the harmonious, sweet, and sour taste of the ‘Krupnoplidna’ variety. The fruits of the ‘Modnitsa’ and ‘Griot Melitopolskyi’ varieties received the highest score (8,7) based on the average sensory parameters. The fruits of these varieties had a delicate texture, the juiciest pulp, and thin skin. Experts singled out the ‘Modnitsa’ and ‘Griot Melitopolskyi’ varieties for their taste qualities. The taste qualities of the fruits of these varieties were rated at 8,9 points. The analysis will help predict the directions of raw material use – for cooling and transportation, for consumption in fresh form, or for food production – and is a tool for optimising post-harvest technological processes in the food industry.
Keywords: taste of fruit raw materials; sweet cherry and cherry fruits; score; ripening time; overall taste perception